Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.5289
|View full text |Cite
|
Sign up to set email alerts
|

AB0036 Association between synovitis and inflammatory citokines serum levels in a cohort of patients affected by primary knee osteoarthritis

Abstract: BackgroundOsteoarthritis (OA) is characterized by progressive loss of cartilage, deterioration of subchondral bone and mild synovial inflammation. Classified for a long time as a non-inflammatory arthropathy, a growing number of evidences has suggested that OA course could be driven by systemic and localized inflammation. In particular, serum levels of Interleukin (IL)-6 have been associated with higher prevalence of osteophytes in older adults with knee OA. Furthermore, high levels of other inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results of this study revealed significant relation between interleukin 17 and WOMAC scale, this was in agreement with [20,21]. The relation between interleukin-17 and disease severity in our cases using Lequesne et al scale also revealed a highly significant relation between them and this was in agreement with [19,22,23].…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study revealed significant relation between interleukin 17 and WOMAC scale, this was in agreement with [20,21]. The relation between interleukin-17 and disease severity in our cases using Lequesne et al scale also revealed a highly significant relation between them and this was in agreement with [19,22,23].…”
Section: Discussionsupporting
confidence: 89%